TEACHERS’ EMOTIONAL INTELLIGENCE AND LEARNER'S PERCEPTIONS OF THEIR TEACHERS’ VERBAL AND NON-VERBAL IMMEDIACY ACROSS TEACHER’S GENDER - Fariba Khabbaz Azar (LIFE: International Journal of Health and Life-Sciences, 2025)
This study investigated the relationship between teachers’ emotional intelligence (EI) and learners’ perceptions of their teachers’ verbal and non-verbal immediacy across gender in the Iranian EFL context. A descriptive-correlational design was used to collect the data from 210 students and 30 teachers who completed the Verbal Immediacy Measure (VIM), the Non-verbal Immediacy Measure (NVIM), and the Emotional Quotient Inventory (EQ-i). The results showed that there was no significant difference in the verbal and nonverbal immediate behavior of the Iranian EFL teachers across their gender. However, there was a significant difference between the male and female teachers’ EI level, and their EI could significantly predict female teachers’ immediacy. The findings suggest that teachers’ EI is an important factor for creating a positive and supportive learning environment for their students, and that gender may moderate the effects of EI on teacher immediacy. The implications for teacher education and professional development are discussed.